2005
DOI: 10.1038/nn1605
|View full text |Cite
|
Sign up to set email alerts
|

ORL1 receptor–mediated internalization of N-type calcium channels

Abstract: The inhibition of N-type calcium channels by opioid receptor like receptor 1 (ORL1) is a key mechanism for controlling the transmission of nociceptive signals. We recently reported that signaling complexes consisting of ORL1 receptors and N-type channels mediate a tonic inhibition of calcium entry. Here we show that prolonged ( approximately 30 min) exposure of ORL1 receptors to their agonist nociceptin triggers an internalization of these signaling complexes into vesicular compartments. This effect is depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
134
2
6

Year Published

2007
2007
2019
2019

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 155 publications
(148 citation statements)
references
References 49 publications
6
134
2
6
Order By: Relevance
“…The mechanisms that control the degradation of Ca v 2.1 are not well understood. It has been shown that Ca v 1.2 and Ca v 2.2 undergo internalization and translocation to lysosome for degradation in response to activation of either the NMDA receptor or the nociceptin receptor (23,24). Therefore, although the mechanisms by which Ca v 2.1 is internalized remain elusive, it is likely that Ca v 2.1 is also sequestered to lysosome for degradation.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms that control the degradation of Ca v 2.1 are not well understood. It has been shown that Ca v 1.2 and Ca v 2.2 undergo internalization and translocation to lysosome for degradation in response to activation of either the NMDA receptor or the nociceptin receptor (23,24). Therefore, although the mechanisms by which Ca v 2.1 is internalized remain elusive, it is likely that Ca v 2.1 is also sequestered to lysosome for degradation.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 All of these mechanisms terminate G protein signaling and thus channel modulation, but in some cases, direct GPCR-Ca V 2 interactions have been demonstrated that result in endocytic removal of the channel from the plasma membrane upon GPCR desensitization. [33][34][35] Inhibition of Ca 2+ Channels by G Protein βγ…”
Section: G Protein Coupled Receptors and Heterotrimeric G Proteinsmentioning
confidence: 99%
“…Voltage-independent inhibition is generally less well characterized and likely comprised of several distinct mechanisms including channel trafficking, phosphorylation and lipid signaling pathways (reviewed in ref. 34,35,40,[43][44][45][46][47][48]. The primary focus of this review is the direct, voltage-dependent inhibition of Ca V 2 channels.…”
Section: Subunits-functional Effectsmentioning
confidence: 99%
See 2 more Smart Citations